Multiresponsive polymer nanoparticles based on disulfide bonds - Wagner, Maximilian; Krieger, Anja; Minameyer, Martin; Hämisch, Benjamin; Huber, Klaus; Drewello, Thomas; Gröhn, Franziska (Macromolecules, 2021)
A disulfide polymer that is triggerable by ultrasound, UV, and redox in aqueous solution and can self-assemble with ionic probe molecules into again multitriggerable assemblies is presented. It is created by oxidative coupling of a branched insoluble thiol to water-soluble ionic thiols. The synthesis via a nanoprecipitation technique results in charged macromolecule particles with adjustable sizes between a few tens and a few hundred nanometers stable in aqueous solution. Macromolecules of different compositions form with pentaerythritol tetrakis(3-mercaptopropionate) as insoluble cross-linkers yielding the polymer backbone, while mercaptopropionic acid, mercaptosuccinic acid, or aminoethane thiol in varying amounts is coupled to the backbone. Molecular and nanoscale switchability of the disulfide macromolecule with UV light, redox potential, and ultrasound is demonstrated. The anionic character of the polymer particles is exploited by electrostatic self-assembly with the tetra-cationic 5,10,15,20-tetrakis-(N-methyl-4-pyridyl)porphyrin and its zinc-metalated derivative, yielding supramolecular composite structures as a model system for delivery. The new type of polymer particles in aqueous solution may pave an alternative way toward multiresponsive and functional materials with potential in medicine and material science.
CRIS-Team Scopus Importer:2021-04-09